Domestikasi Tumbuhan Bemban (Donax Canniformis) Untuk Keberlanjutan Usaha Kerajinan Bili Di Desa Lampanah Tunong, Aceh Besar - Yasar, Muhammad; Hafsah, Siti; Juliaviani, Noratun (DCS: Jurnal Pengabdian Masyarakat, 2024)
The bemban plant (Donax canniformis) has important meaning for the community in Lampanah Tunong Village, Indrapuri District, Aceh Besar Regency. Together with 4 (four) other villages around it, this village has become a center for woven bemban crafts with production products that are typical superior products for Aceh Besar Regency. Apart from supporting the development of the tourism sector and creative industry, this woven bemban craft product has been able to improve the economy and welfare of the local community. The lack of implementation of the concept of sustainable development (sustainable development) has resulted in vulnerability to the continuity of this highly prospective business. The provision of raw materials that completely relies on availability in nature has resulted in the increasingly extinct population of burden plants. The rate of handicraft production which is not commensurate with the ability of natural plant reproduction has caused the community to have to bring in raw materials from outside the village. This of course has an impact on increasing production costs and reducing opportunities for profits. Without systematic and strategic efforts, it is feared that availability from outside the village will also threaten its sustainability. To overcome this, the Service Team offers a concrete solution in the form of domestication efforts by transforming wild bemban plants into cultivated bemban plants through the introduction of cultivation techniques, nurseries and cultivation demonstration plots as well as improving and developing marketing techniques through product diversification and the use of digital marketing. The methods used include: counseling/tutorials and direct practice in the field with stages consisting of: preparation, coordination, implementation, coaching, and trials/evaluation. Through this service activity, it is hoped that the sustainability of the bemban woven craft business will be realized (SDGs 11), increase economic growth (SDGs 8), reduce poverty (SDGs 1) and improve the welfare (SDGs 3) of the community, especially partner craftsmen (SDGs 17).